PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN CONTEXTUAL TEACHING LEARNING DAN DISCOVERY LEARNING PADA KONSEP INTERAKSI MAHLUK HIDUP - Maemunah, Lia; Wrsono, Warsono (Universitas Galuh, 2019)
The purpose of this study was to determine differences in student learning outcomes using Contextual Teaching Learning (CTL) and Discovery Learning (DL) on the concept of Interaction in Living things. The research method used quasi-experiments. Data collection techniques using multiple choice tests. The population in this study were four classes of eighth grade students of YPI Al-Huda Middle School in Tasikmalaya City. The sample of this study is two classes, they are class VIIA and class VIIB are determined using purposive sampling techniques. Data analysis techniques using the t test. Based on data analysis, the results of the study concluded that there were differences in student learning outcomes using Contextual Teaching Learning (CTL) and Discovery Learning (DL) on the concept of Interaction in Living ThingsKeywords : contextual teaching learning (CTL) model,Â discovery learning (DL),Â learning outcomes.